2017
DOI: 10.3747/co.24.3216
|View full text |Cite
|
Sign up to set email alerts
|

Contextualizing the Use of Oncologic Imaging within Treatment Phases: Imaging Trends and Modality Preferences, 2000–2014

Abstract: BackgroundIn the present study, we retrospectively evaluated the use of tomographic imaging in adult cancer

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…[5] The utilization of testing in general-and high cost, advanced diagnostic imaging such as CT, MRI, and PET in particular-continues to increase in various phases of breast cancer management. [11][12][13] As we, and others, pursue research aimed at quantifying from claims data the use and appropriateness of testing in breast cancer management, the differentiation of testing specifically for cancer recurrence in the breast cancer population over background rates of testing in non-cancer populations will continue to be important. In the absence of a "gold standard" it is reassuring that we found similar, if not identical, rates of additional testing regardless of method adopted.…”
Section: Discussionmentioning
confidence: 99%
“…[5] The utilization of testing in general-and high cost, advanced diagnostic imaging such as CT, MRI, and PET in particular-continues to increase in various phases of breast cancer management. [11][12][13] As we, and others, pursue research aimed at quantifying from claims data the use and appropriateness of testing in breast cancer management, the differentiation of testing specifically for cancer recurrence in the breast cancer population over background rates of testing in non-cancer populations will continue to be important. In the absence of a "gold standard" it is reassuring that we found similar, if not identical, rates of additional testing regardless of method adopted.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, it has been demonstrated that tumor size in avascular phase is limited to a diameter of 1 to 2 millimeter and tumor cell population is limited [8], however, the tumor growth in absence of mechanical barriers or therapies is extremely progressive during the Mechanisms involved in tumor growth engages complex multicellular dynamics in different spatio-temporal scales including intracellular, intercellular and extracellular scales [9]. Despite the helpful understandings of tumor growth processes obtained by experiments tied up with recent imaging modalities [10,11], it is hard to evaluate all the various multi-scale phenomena occurring during tumor growth in experimental studies. In this context, a multi-scale modeling embedding various spatio-temporal scales involving in tumor growth would make an acceptable sight of such intricate procedure.…”
Section: Introductionmentioning
confidence: 99%